"Continent-wide" sports spectacles: The "multiple host format" of Euro 2020 and United 2026 and its implications. Issue 2 (15th March 2019) - Ludvigsen, Jan A.
Abstract: Predominantly, sport mega-events (SMEs) have been staged in one or, occasionally, two countries. However, the 2020s, symbolize a decade where two of the largest SMEs will take up a geographically unique format, and be staged in 12 and 3 host countries, respectively. This article visits the "multiple host format" and examines three key organizational implications of this alternate format. These include grievances for event attendees, less financial risk concerning new stadia/infrastructure, and challenges with regards to security planning. Overall, the format represents an including and innovative solution, in a time wherein SMEs have been questioned for excessive expenditure and "unsuited" hosts.